ChemInform Abstract: An Efficient, Stable and Reusable Palladium Nanocatalyst: Chemoselective Reduction of Aldehydes with Molecular Hydrogen in Water. Issue 38 (September 2016) - Kotha, Surya Srinivas; Sharma, Nidhi; Sekar, Govindasamy
Abstract: Pd‐nanoparticles stabilized by a binaphthyl‐backbone are used for the chemoselective reduction of aldehydes to give the corresponding benzylic alcohols.